PENJATUHAN PIDANA BERSYARAT TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN - Adia Nugraha (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
abstractBasic considerations of criminal law judges in imposing conditional on the perpetrators of criminal acts of persecution are juridical considerations, namely the fulfillment of a minimum of two items of evidence in the trial, the judge considered that there are justification, an excuse and a reason for removing the judge the prosecution to convict on parole. Beside the judges also look at the background of the events of the crime as a whole as well as the attitudes and actions of the defendant in the community daily. The defendant did cause by the maltreatment victims who are not acting in good faith to the defendant as a guarantor of loans receivable in the pawnshop and the defendant has been helping victims to get a loan. Court decisions that criminalize conditional against an abuser are deemed not in accordance with the justice community because judges are less sensitive to the suffering of victims of the crime of persecution by the defendant. The judge should impose a more optimal criminal defendant, given the criminal acts of persecution that resulted in physical harm to the victim in the form of bruises and abrasions due to blunt impact. Keywords: Imposition, Conditional Punishment, PersecutionabstrakDasar pertimbangan hukum hakim dalam menjatuhkan pidana bersyarat terhadap pelaku tindak pidana penganiayaan adalah pertimbangan yuridis sebagaimana diatur Pasal 184 KUHAP, hakim menilai bahwa terdapat alasan pembenar, alasan pemaaf dan alasan penghapusan penuntutan bagi hakim dalam menjatuhkan pidana bersyarat. Selain itu hakim juga melihat peristiwa yang melatar belakangi perbuatan pidana tersebut secara keseluruhan serta sikap dan perbuatan terdakwa sehari-harinya dalam masyarakat. Terdakwa melakukan penganiayaan disebabkan oleh korban yang tidak beritikad baik kepada terdakwa sebagi penjamin hutang piutang di Pegadaian dan terdakwa telah menolong korban untuk mendapatkan pinjaman. Putusan pengadilan yang menjatuhkan pidana bersyarat terhadap pelaku tindak pidana penganiayaan dipandang belum sesuai dengan keadilan masyarakat karena hakim kurang sensitif terhadap penderitaan korban akibat tindak pidana penganiayaan oleh terdakwa. Hakim semestinya menjatuhkan pidana yang lebih optimal kepada terdakwa, mengingat tindak pidana penganiayaan yang dilakukan tersebut mengakibatkan penderitaan fisik pada korban berupa luka memar dan lecet akibat benturan benda tumpul. Kata Kunci: Penjatuhan Pidana, Hukuman Bersyarat, Penganiayaan